John Bull reading the Extraordinary Red Book. - (:unkn) unknown (Tegg, Thomas, 1816)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Politicians salaries; Great Britain -- Politics and government -- 1800-1837; John Bull (Symbolic character)